2014
DOI: 10.1016/j.rmed.2014.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic pulmonary calcification: State-of-the-art review focused on imaging findings

Abstract: Metastatic pulmonary calcification (MPC) is a subdiagnosed metabolic lung disease that is commonly associated with end-stage renal disease. This interstitial process is characterized by the deposition of calcium salts predominantly in the alveolar epithelial basement membranes. MPC is seen at autopsy in 60-75% of patients with renal failure. It is often asymptomatic, but can potentially progress to respiratory failure. Chest radiographs are frequently normal or demonstrate confluent or patchy airspace opacitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
159
1
21

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(181 citation statements)
references
References 53 publications
0
159
1
21
Order By: Relevance
“…Accordingly, these two ions have a particularly important relationship in biology and can exist in multiple forms (ratios) such as mono, di, and tri-calcium phosphate (ratios from 0.5 to 1.5) [2]. Recent studies have suggested that various forms of nano-Calcium-Phosphate (CaP) synthesized by the body are associated with functional mineralization of bone and pathological calcification of vascular smooth muscle [37]. Nano-sized hydroxyapatite (nano-HAp) is generated endogenously by osteoblasts in the form of matrix vesicles as the initiator of bone formation in the skeleton, [8] as well as in pathological calcification of cartilage and vasculature [912] and can be deposited in soft tissues in the form of dystrophic and metastatic calcifications, [13, 14] although the origins are not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, these two ions have a particularly important relationship in biology and can exist in multiple forms (ratios) such as mono, di, and tri-calcium phosphate (ratios from 0.5 to 1.5) [2]. Recent studies have suggested that various forms of nano-Calcium-Phosphate (CaP) synthesized by the body are associated with functional mineralization of bone and pathological calcification of vascular smooth muscle [37]. Nano-sized hydroxyapatite (nano-HAp) is generated endogenously by osteoblasts in the form of matrix vesicles as the initiator of bone formation in the skeleton, [8] as well as in pathological calcification of cartilage and vasculature [912] and can be deposited in soft tissues in the form of dystrophic and metastatic calcifications, [13, 14] although the origins are not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…2 Among those who have symptoms, the manifestations can include progressive dyspnea, hypoxemia, hemoptysis and, rarely, alveolar hemorrhage and fulminant respiratory insufficiency. 3 The differential diagnosis includes end-stage renal disease, malignancies (such as multiple myeloma) and dystrophic pulmonary calcification (Appendix 2, available at www.cmaj.ca/lookup/ suppl/doi:10.1503/cmaj.150778/-/DC1). 3,4 High-resolution CT typically shows poorly defined centrilobular nodules with ground glass opacities 3-10 mm in diameter.…”
mentioning
confidence: 99%
“…3 The differential diagnosis includes end-stage renal disease, malignancies (such as multiple myeloma) and dystrophic pulmonary calcification (Appendix 2, available at www.cmaj.ca/lookup/ suppl/doi:10.1503/cmaj.150778/-/DC1). 3,4 High-resolution CT typically shows poorly defined centrilobular nodules with ground glass opacities 3-10 mm in diameter. 2 CT detects existing calcium deposits that may be inactive, whereas bone scintigraphy identifies areas of active calcium deposition.…”
mentioning
confidence: 99%
See 2 more Smart Citations